Men in the Middle. Local Priests in Early Medieval Europe - Patzold, Steffen; van van Rhijn, Carine (De Gruyter, 2016)
This volume studies local priests as central players in small communities of early medieval Europe. On the one hand, manuscript evidence shows their knowledge, expertise and potential to teach, whereas charter collections shed light on local priests as active members of networks of the locally powerful. By combining both approaches and covering most of early medieval Europe, this book is the first to offer a comprehensive overview of the subject.